Assessment of Diversity among Important Brinjal (Solanum melongena) Cultivars Using Morphological Markers. (18th October 2022) - Younas, Zohaib; Naseer, Samar; Kazmi, Abeer; Ali, Amir; Wahab, Abdul; Sultana, Tahira; Shoukat, Irsa; Hameed, Asma; Afzal, Mubashar; Mashwani, Zia-Ur-Rehman; Rahimi, Mehdi
Abstract : Background . Solanum melongena is a medicinally important vegetable crop that belongs to the family Solanaceae, which is cultivated worldwide. Methodology . In the present study, 22 eggplant varieties from the different ecogeographical regions were evaluated for nine quantitative and twenty-two qualitative morphological characters. A significant divergence was observed in all characters and wide regional variations for plant characteristics, flower, and fruit characteristics. Principle component analysis (PCA) was performed using PAST3 software to determine the relationship among eggplant accessions. Results . The principal component analysis showed that the first two principal component axes explained 97.17% of the total multivariate variation. Cluster analysis using the Unweighted Pair Group Method of Arithmetic Means (UPGMA) grouped the 22 eggplant accessions into two main clusters based on similarities in morphological characteristics. The study showed that the Solanum melongena accessions belonging to Pakistan and other geographical regions of the world possess marked variation in fruit weight, fruit shape, fruit color, leaf spine, number of locules in fruit, plant height, and flower color. Conclusion . Based on morphological diversity, the best cultivars of eggplant that show better yield can be selected for farmers.